Stigmatization of new religious movements - Martinovich, Vladimir A. (Journal of the Belarusian State University. Sociology, 2019)
The present article is devoted to the analysis of the variety of stigmatization theories and the possibilities of their application to the process of stigmatization of new religious movements. The main fundamental works of Edwin Lemert, Howard Becker, Erwin Goffman and James Aho are represented, as well as a group of minor studies of the reaction of religious groups to the public characterization of them as deviant groups. Special attention is paid to the author’s theory of the process of identification of religious organizations as a master level of the stigmatization of new religious movements. The last one process is presented as regular appearing malfunction of the process of identification of religious groups, which leads to the public attribution to them of different labels with negative connotations. Several irregular situations are analyzed in which a particular religious group can imagine itself as being persecuted of stigmatized without relevant foundations for this selfperception. There are identified main factors of socio cultural context influencing the limitations of the negative influence of the process of stigmatization of new religious movements in XX–XXI centuries.